Influence of psychological attachment patterns on periodontal disease – a pilot study with 310 compliant patients. (22nd September 2013) - Graetz, Christian; Ehrenthal, Johannes C.; Senf, Dana; Semar, Katrin; Herzog, Wolfgang; Dörfer, Christof E.
Abstract: Objectives: Psychosocial variables have received increased attention in periodontology. Attachment theory adds to known risk factors by linking early interactional experiences with adult tendencies of stress‐regulation, health behaviour, symptom reporting, and healthcare utilization. The study investigates associations between attachment patterns and periodontal parameters. Methods: Within the context of a longitudinal study on periodontal diseases, 310 patients with aggressive (AgP) and chronic periodontitis (CP) filled out questionnaires on psychological attachment patterns. The influence of attachment style on health behaviour, treatment attendance and utilization, and periodontal variables was tested. Results: We found associations between psychological attachment anxiety on smoking and higher number of session use, independent of disease severity, which was more pronounced for women. Patients with higher attachment avoidance attended periodontal treatment later when diagnosed with CP and earlier with AgP. For men, we found differential associations for attachment avoidance and anxiety and number of teeth at beginning of treatment. Conclusion: Psychological attachment patterns are a promising target for understanding periodontal disease in addition to known psychosocial risk factors.